Elevating Science Education: Igniting Learning through Mindmapping and Collaborative Strategies - Rosyida, Nabila; Evitasari, Atika Dwi; Utaminingtyas, Siwi (The Indonesian Institute of Science and Technology Research, 2023)
This study aimed to enhance the learning outcomes of fifth-grade students in Science by implementing the Think Pair Share (TPS) model with a foundation in Mindmapping. The research was conducted at a particular elementary school and involved two cycles of instructional intervention. The study's objectives included assessing the impact of the TPS model on student learning outcomes, evaluating teacher and student engagement, and refining the instructional approach for improvement. The research employed mixed methods and quantitative and qualitative data collection techniques. Data was gathered through test scores, observation of teacher and student activities, and reflective discussions. The study found that students needed to improve their learning outcomes before implementing the TPS model due to less interactive teaching methods. However, following the introduction of the TPS model coupled with Mindmapping, there was a significant improvement in learning outcomes. The first cycle recorded an average score of 65, with 46.25% achieving the mastery standard. In contrast, the second cycle saw remarkable enhancement, with an average score of 84.42 and 88.46% of students meeting the mastery standard. Observations also indicated substantial improvements in both teacher and student engagement. The teacher's ability to foster motivation, clarify learning objectives, and deliver effective teaching improved significantly. Similarly, students displayed more active participation in learning, paying closer attention, engaging in discussions, and demonstrating better comprehension. In conclusion, implementing the TPS model integrated with Mindmapping techniques led to notable enhancements in student learning outcomes and engagement in Science education. This approach facilitated collaborative learning, boosted critical thinking, and improved classroom experience. The study underscores the efficacy of interactive teaching methodologies in elevating student achievements and offers insights for educational practitioners seeking innovative strategies to foster effective learning environments.